Investigations into the benefits of base isolation for non-symmetric rigid blocks. - Contento, A.
In this paper the influence of base isolation on the behaviour of a work of art has been analysed. To make things more realistic, the work of art has been modelled with a non-symmetrical rigid body, sitting on a base that is connected to a visco-elastic device, which represents the passive control system. To prevent the breaking of the isolation device, security stops have been introduced to limit the displacement of the oscillating base to a maximum safety value. All analyses have been carried out comparing the behaviour of the non-isolated and the isolated non-symmetric rigid body subject to impulsive and seismic excitations. The analysis is particularly focused on the effects of the eccentricity of the rigid body and on the presence of the security stops. Generally, base isolation improves the behaviour of the system while the presence of an eccentricity makes the performance of the system worse with respect to the symmetric rigid body. Moreover the security stops, although they preserve the isolator devices, cause a worsening in the performance of the systems.
Keywords: Base isolation; Non-symmetric rigid block; Security stops; Eccentricity; Impulse; Seismic excitation